Reductive detoxification as a mechanism of fungal resistance to singlet oxygen-generating photosensitizers. - Daub, M E (1992)
Fungi that are resistant or sensitive to the singlet oxygen-generating toxin cercosporin were assayed for their ability to detoxify it by reduction. Cercosporin reduction was assayed microscopically by using bandpass filters to differentiate between fluorescence emission from cercosporin and reduced cercosporin. Hyphae of the resistant Cercospora and Alternaria species emitted a green fluorescence, indicative of reduced cercosporin. Hyphae of nonviable cultures and of cercosporin-sensitive fungi did not reduce cercosporin. Sensitive fungi occasionally reduced cercosporin when incubated with reducing agents that protect against cercosporin toxicity. Cercosporin could not be efficiently photoreduced in the absence of the fungus. Cercospora species were also resistant to eosin Y but were sensitive to rose bengal. Microscopic observation demonstrated that Cercospora species were not capable of reducing rose bengal but were capable of reducing eosin Y. These observations were supported by in vitro electrochemical measurements that revealed the following order with respect to ease of reduction: cercosporin >> eosin Y > rose bengal. The formal redox potential (E 0') of cercosporin at pH 7.5 was found to be -0.14 V vs. the normal hydrogen electrode. We conclude that Cercospora species protect themselves against cercosporin by the reduction and detoxification of the toxin molecule.